CUPS Update From the Citrus Research and Education Center - Arnold Schumann; Laura Waldo; Chris Oswalt; Napoleon Mariner; Timothy A. Ebert; Perseveranca Mungofa; Shankar Shrestha (EDIS, 2022)
In this update to our previous report of CREC CUPS research published in Citrus Industry (November 2020; https://tinyurl.com/CUPS-2020), we will discuss red grapefruit production in 2021/22, which is the most recent of seven consecutive seasons.